Thermographic imaging in sports and exercise medicine: A Delphi study and consensus statement on the measurement of human skin temperature. (October 2017) - Moreira, Danilo Gomes; Costello, Joseph T.; Brito, Ciro J.; Adamczyk, Jakub G.; Ammer, Kurt; Bach, Aaron J.E.; Costa, Carlos M.A.; Eglin, Clare; Fernandes, Alex A.; Fernández-Cuevas, Ismael; Ferreira, José J.A.; Formenti, Damiano; et al.
Abstract: The importance of using infrared thermography (IRT) to assess skin temperature (tsk ) is increasing in clinical settings. Recently, its use has been increasing in sports and exercise medicine; however, no consensus guideline exists to address the methods for collecting data in such situations. The aim of this study was to develop a checklist for the collection of tsk using IRT in sports and exercise medicine. We carried out a Delphi study to set a checklist based on consensus agreement from leading experts in the field. Panelists (n = 24) representing the areas of sport science (n = 8; 33%), physiology (n = 7; 29%), physiotherapy (n = 3; 13%) and medicine (n = 6; 25%), from 13 different countries completed the Delphi process. An initial list of 16 points was proposed which was rated and commented on by panelists in three rounds of anonymous surveys following a standard Delphi procedure. The panel reached consensus on 15 items which encompassed the participants' demographic information, camera/room or environment setup and recording/analysis of tsk using IRT. The results of the Delphi produced the checklist entitled "Thermographic Imaging in Sports and Exercise Medicine (TISEM)" which is a proposal to standardize the collection and analysis of tsk data using IRT. It is intended that the TISEM can also be applied to evaluate bias in thermographic studies and to guide practitioners in the use of this technique. Highlights: It was produced a checklist to assess skin temperature using infrared thermography. The checklist contributes to the most appropriate application of this technique. This checklist can be applied by wide array of end-users.